Research Strategies for Precise Manipulation of Micro/Nanoparticle Drug Delivery Systems Using Microfluidic Technology: A Review - Liu, Jie; Fu, Qinghui; Li, Qin; Yang, Yani; Zhang, Yue; Yang, Kaili; Sun, Guohao; Luo, Jiayu; Lu, Weigen; He, Jun (Pharmaceutical Fronts, 2024)
Microfluidic technology facilitates precise control over fluid mixing and interactions between the components, including self-assembly and precipitation. It offers new options for accurately manufacturing particles and holds significant potential in advancing micro/nanoparticle drug delivery systems (DDSs). Various microchannel/microfluidic chips have been explored to construct micro/nanoparticle DDSs. The precise manipulation of particle size, morphology, structure, stiffness, surface characteristics, and elasticity through microfluidic technology relies on specific microchannel geometrical designs and the application of exogenous energy, adhering to the principles of fluid motion. Consequently, this enables reproducible control over critical quality attributes (CQAs), such as particle size and distribution, encapsulation efficiency, drug loading, in vitro and in vivo drug delivery profiles, Zeta potential, and targeting capabilities, for micro/nanoparticle DDSs. In this review, we categorize microfluidic techniques and explore recent research developments in novel microchannel structures spanning the past 5 years (2018–2023) and their applications in micro/nanoparticle DDSs. Additionally, we elucidate the latest manipulation strategies of microfluidic techniques that impact foundational structures related to the CQAs of micro/nanoparticle DDSs. Furthermore, we offer insights into the industrial applications and challenges microfluidic techniques face in the context of novel micro/nanoparticle DDSs.
Keywords: microfluidic technology; micro/nanoparticle drug delivery systems; precision manufacturing; industrialization